1974
DOI: 10.1136/jcp.27.5.348
|View full text |Cite
|
Sign up to set email alerts
|

Asymptomatic liver disease in hepatitis B antigen carriers

Abstract: srNopsis Thirty-four healthy blood donors, found to be persistent HBAg carriers, have been investigated by means of serial liver function tests, bromsulphthalein (BSP) retention, and liver biopsy. Thirty-one of the donors had histological abnormalities including one with cirrhosis, three with chronic aggressive hepatitis, and 11 with chronic persistent hepatitis. In 13 biopsies there were focal areas of necrosis in the liver parenchyma. Serial liver function tests revealed abnormalities in each ofthe donors w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
2

Year Published

1975
1975
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 20 publications
3
15
2
Order By: Relevance
“…The findings in these carriers are similar to those reported by other authors in chronic HBV carriers found at blood donation [1][2][3]. These reports relate solely to volunteer blood donors, although only a minority were UK donors.…”
Section: Discussionsupporting
confidence: 81%
“…The findings in these carriers are similar to those reported by other authors in chronic HBV carriers found at blood donation [1][2][3]. These reports relate solely to volunteer blood donors, although only a minority were UK donors.…”
Section: Discussionsupporting
confidence: 81%
“…Our follow-up study of the carriers with abnormal LFTs showed that, when the LFTs remained abnormal, severe histological liver abnormalities, most ly in the form of chronic aggressive hepa titis and/or cirrhosis, were present. On the other hand, in the carriers in which the LFTs became normal, no histological liver abnor mality was observed; this agrees with other published reports [23,32]. Several writers [4,10,30], however, reported severe liver disease in subjects with normal LFTs.…”
Section: Hbsag Subtypessupporting
confidence: 80%
“…This is in accord with Couroucé-Pauty and Plançon [5], who found 80 and 10% abnormal LFTs in HBeAg and anti-HBe-positive carriers, re spectively. Without regarding the HBeAg/ anti-HBe system, others [5,22,23,28,30,32] reported abnormal LFTs in about 20-50% of HBsAg carriers. Our follow-up study of the carriers with abnormal LFTs showed that, when the LFTs remained abnormal, severe histological liver abnormalities, most ly in the form of chronic aggressive hepa titis and/or cirrhosis, were present.…”
Section: Hbsag Subtypesmentioning
confidence: 99%
See 1 more Smart Citation
“…7 Tests for e antigen and e antibody were performed by a standard immunodiffusion technique.3 The two test sera used gave reactions of complete identity against reference sera kindly provided by Dr J 0 Nielsen, of Copenhagen. For immune electron microscopy the sera were mixed with anti-HBs precipitating antisera and incubated overnight at 4°C.…”
Section: Methodsmentioning
confidence: 99%